Skills-specific competitive performance profiles of winter polyathlonists - Farbey, V. V.; Ponomarev, G. N. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to profile the skills-specific competitive fitness of the 21-25 year-old athletes engaged in winter polyathlon based on a factor analysis of the key competitive performance rates, with 15 World Class Masters of Sport, 25 Masters of Sport, 22 Candidate Masters of Sport and 24 Class I-II Athletes sampled for the study. The comparative analysis of the skills-specific factorial competitive process profiles of the sample showed significant intergroup differences. It was found among other things that the contributions of specific events to total scores are skill-group-specific. In case of top-skilled athletes, the top-scoring events were all-round skiing followed by ski race and shooting. In case of the average-skilled athletes, the success was determined by speed endurance, pull-ups, shooting skills, total points, 5/10km ski races and strength endurance. And the low-skilled athletes` competitive performance was driven by 10km ski race, pull-ups, strength endurance, functional fitness, shooting skills and total standing in all-round skiing.